2010
DOI: 10.1051/kmae/2010014
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary data on the feeding habits of the endemic speciesSynodontis koensisPellegrin, 1933 (Siluriformes, Mochokidae) in a West African River (Sassandra River Basin, Côte d’Ivoire)

Abstract: Key-words:Synodontis koensis, endemic species, feeding habit, Sassandra River, Côte d'Ivoire In the implementation of programs for protection and management of ichthyofauna, endemic species should have high priority in the conservation measures. Their fishery should be based on intimate knowledge of their ecology and biology. Feeding habits of the endemic Mochokid Synodontis koensis were assessed in the Sassandra River (Côte d'Ivoire) in relation to the study zone, the specimen sex and size, and the season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Thus, it seems that feeding intensity and type of items are directly correlated with digestion time (Lagler, Bardach & Miller, ; Fange & Grove, ; Grove & Crawford, ). Other studies have indicated that species within the genus Synodontis are omnivorous fishes (Lalèyè et al ., ; Koné et al ., ; Diomandé, Doumbia & Gourene, ; Yao et al ., ). Furthermore, the low intestinal coefficient confirms that species belongs to the group of omnivorous fishes as already noted by Fryer & Iles (), Paugy () and Koné et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, it seems that feeding intensity and type of items are directly correlated with digestion time (Lagler, Bardach & Miller, ; Fange & Grove, ; Grove & Crawford, ). Other studies have indicated that species within the genus Synodontis are omnivorous fishes (Lalèyè et al ., ; Koné et al ., ; Diomandé, Doumbia & Gourene, ; Yao et al ., ). Furthermore, the low intestinal coefficient confirms that species belongs to the group of omnivorous fishes as already noted by Fryer & Iles (), Paugy () and Koné et al .…”
Section: Discussionmentioning
confidence: 97%
“…Fish scales were also found in the diet of S . p unctifer as was reported in other Synodontis species (Yatabary, ; Diomandé, Gourene & Tito De Morais, ; Yao et al ., ). This dietary item is known to be a source of calcium (Vilella, Becker & Hartz, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fish classification into herbivorous, invertivorous, omnivorous, piscivorous, and planktivorous categories were made following Trewavas (1983), King (1994), Diomandé et al (2009), Yao et al (2010, Kouamélan et al (2012), andFishBase (2013). Species richness (which is the number of species sampled at each sampling zone) was used to determine the structure and ecological dynamics of the community.…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, ce cours d'eau ivoirien est soumis à plusieurs pressions anthropiques qui menacent l'existence de cette espèce. Kouamé et al (2008) et Yao et al (2010) ont signalé des menaces de la pollution agricole et industrielle liées aux exploitations agro-industrielles réalisées sur le bassin versant du fleuve Sassandra. A cela s'ajoute la pression de la pêche sur le lac de barrage de Buyo qui échappe aux mesures de contrôle des gestionnaires.…”
Section: Introductionunclassified